OP0268-HPR RHEUMATIC DISEASE PATIENTS' PREFERENCES IN ADVERSE DRUG REACTION INFORMATION REGARDING BIOLOGICS. (2nd June 2020) - Weits, G.; Kosse, L.; Vonkeman, H.; Spuls, P.; Van den Bemt, B.; Tas, S.; Hoentjen, F.; Nurmohamed, M.; Van Doorn, M.; Van Puijenbroek, E.; Jessurun, N.
Abstract : Background: Patient-reported outcomes (PROs) are increasingly used in studies and medical practice to obtain information on patients' perspectives towards their treatment or disease. However, study outcomes are primarily directed at and shared with healthcare professionals, even though the results may also be relevant for patients. Objectives: The objective of this study was to obtain insight in which results patients with immune-mediated inflammatory diseases (IMIDs), including inflammatory rheumatic disease patients, prefer to receive after participating in the Dutch Biologic Monitor. Methods: The Dutch Biologic Monitor is a PRO-based prospective cohort event monitoring study focused on adverse drug reactions (ADRs) [1]. A survey was conducted among the participants of the Dutch Biologic Monitor who wanted to be informed about the results. Patients' preferences were identified using twelve statements and rated with five-point Likert-type scales. Averages described the preference per statement. Preference for the results per IMID or altogether was assessed using Mann-Whitney U Test. Results: Respondents (N=591, response rate 67.6%) preferred results per IMID over aggregated results ( p =<0.001). Information on whether patients with the same IMID experience ADRs (average 4.5), which biologics are most likely to cause ADRs (4.4) and whether the ADRs subside or disappear (4.4) were regarded as most interesting. Outcomes of patients with other IMIDs (3.5), patient characteristics (3.7) and injection site reactions (3.8) were least interesting. Conclusion: Participants of the Dutch Biologic Monitor that use a biologic for their IMID prefer to receive ADR information tailored to their own biologic and IMID. Furthermore, they want to obtain insight in the course of ADRs. Therefore, we advocate to generate disease-specific information on ADRs for IMID patients. References: [1]Kosse LJ, Jessurun NT, Hebing RCF, Huiskes VJB, Spijkers KM, van den Bemt BJF, et al. Patients with inflammatory rheumatic diseases: quality of self-reported medical information in a prospective cohort event monitoring system. Rheumatol. published on 30 Sept 2019. doi: 10.1093/rheumatology/kez412. Disclosure of Interests: Gerda Weits: None declared, Leanne Kosse: None declared, Harald Vonkeman: None declared, Phyllis Spuls Grant/research support from: Departmental independent research grant for TREAT NL registry LeoPharma December 2019; Contract support: I am involved in performing clinical trials with many pharmaceutical industries that manufacture drugs used for the treatment of e.g. psoriasis and atopic dermatitis for which we get financial compensation paid to the department/hospital, Consultant of: Consultancies in the past for Sanofi 111017 and AbbVie 041217 (unpaid), Bart van den Bemt Grant/research support from: UCB, Pfizer and Abbvie, Consultant of: Delivered consultancy work for UCB, Novartis and Pfizer, Speakers bureau: Pfizer, AbbVie, UCB, Biogen and Sandoz., Sander Tas: None declared, Frank Hoentjen Grant/research support from: Received grants from Dr Falk, Janssen-Cilag, and AbbVie., Consultant of: Served on advisory boards, or as speaker or consultant for AbbVie, Celgene, Janssen-Cilag, MSD, Takeda, Celltrion, Teva, Sandoz, and Dr Falk, Speakers bureau: Served on advisory boards, or as speaker or consultant for AbbVie, Celgene, Janssen-Cilag, MSD, Takeda, Celltrion, Teva, Sandoz, and Dr Falk, Michael Nurmohamed Grant/research support from: Not related to this research, Consultant of: Not related to this research, Speakers bureau: Not related to this research, Martijn van Doorn Grant/research support from: Unrestricted grants, advisory board, speaker fees and/or other (investigator) from Novartis, Abbvie, Janssen Cilag, Leopharma and Pfizer, Speakers bureau: Unrestricted grants, advisory board, speaker fees and/or other (investigator) from Novartis, Abbvie, Janssen Cilag, Leopharma and Pfizer, Eugène van Puijenbroek: None declared, Naomi Jessurun: None declared